Editorial: Microbial communities in fermented products: current knowledge and future prospects - Papademas, Photis; Paramithiotis, Spiros; Aspri, Maria; Bintsis, Thomas; Anagnostopoulos, Dimitrios A.; Tsaltas, Dimitrios (My University, 2024)
Fermentation has been applied since antiquity for the production of palatable food with excellent preservation capacity. It is driven by microbial consortia that are adapted to the nutrient and energy sources of the raw materials and specific ambient conditions. Through the interplay between abiotic and biotic factors, the production of fermented products with enhanced organoleptic characteristics, preservation potential and nutritional value, is achieved. Assessment of the microbial communities that drive fermentation has attracted significant scientific attention. Characterization of the physicochemical properties of the raw materials employed, identification of the microorganisms that dominate or participate as secondary microbiota in these microecosystems, their metabolic potential, as well as the effect that the fermentation conditions may have on the biotransformations that take place during fermentation, have been in the epicenter of scientific scrutiny for decades. The aim of this Research Topic was to provide with a collection of articles that would facilitate our understanding on the aforementioned topics, identify research gaps and pave the road for future research.
Keywords: next generation sequencing; culture-dependent techniques; culture-independent techniques; fermentation; microbial communities; microbial interaction